Principles of practice parameters for the treatment of sleep disordered breathing in the elderly and frail elderly: the consensus of the International Geriatric Sleep Medicine Task Force. Issue 4 (28th July 2016) - Netzer, Nikolaus C.; Ancoli-Israel, Sonia; Bliwise, Donald L.; Fulda, Stephany; Roffe, Christine; Almeida, Fernanda; Onen, Hakki; Onen, Fannie; Raschke, Friedhart; Martinez Garcia, Miguel Angel; Frohnhofen, Helmut
Sleep disordered breathing (SDB) is a leading cause of morbidity worldwide. Its prevalence increases with age. Due to the demographic changes in industrial societies, pulmonologists and sleep physicians are confronted with a rapidly growing number of elderly SDB patients. For many physicians, it remains unclear how current guidelines for SDB management apply to elderly and frail elderly patients. The goal of this consensus statement is to provide guidance based on published evidence for SDB treatment in this specific patient group. Clinicians and researchers with expertise in geriatric sleep medicine representing several countries were invited to participate in a task force. A literature search of PubMed from the past 12 years and a systematic review of evidence of studies deemed relevant was performed. Recommendations for treatment management of elderly and frail elderly SDB patients based on published evidence were formulated via discussion and consensus. In the last 12 years, there have been surprisingly few studies examining treatment of SDB in older adults and even fewer in frail older adults. Studies that have been conducted on the management of SDB in the older patient population were rarely stratified for age. Studies in SDB treatment that did include age stratification mainly focused on middle-aged and younger patient groups. Based on the evidence that is available, this consensus statement highlights the treatment forms that can be recommended for elderly SDB patients and encourages treatment of SDB in this large patient group. An overview of the research in the field of and clinical guidelines for the treatment of SDB in elderly patients http://ow.ly/pfjr301FQur